Meta-analysis of individual participant data: rationale, conduct, and reporting. (5th February 2010) - Riley, Richard D; Lambert, Paul C; Abo-Zaid, Ghada
Abstract : The use of individual participant data instead of aggregate data in meta-analyses has many potential advantages, both statistically and clinically. Richard D Riley and colleagues describe the rationale for an individual participant data meta-analysis and outline how to conduct this type of study